GENDER PERSPECTIVE IN THE ESSAY COLLECTION MEN COBLONG BY OKA RUSMINI - Thera Widyastuti (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
Oka Rusmini is a female writer and journalist whose works mostly about women and their problems. Her essay collection Men Coblong, published in 2019, features a woman named Men Coblong who experiences various events in her daily life. As a mother, Men Coblong acts as a social observer of events around her, particularly those pertain to education system. The research problem is how to reflect the gender perspective through the main character. This is qualitative research and it employs descriptive analysis method. As the theoretical bases, it applies theory of gender and sociology of literature. The writer depicts Men Coblong as a person who is sensitive toward social situations that happen within the society. She tries to make herself as a woman who plays a dual role, which are in the domestic and public are.